2020
DOI: 10.1123/ijspp.2019-0290
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning: Improved Cycling Performance Despite Nocebo Expectation

Abstract: Purpose: Ischemic preconditioning (IPC) through purposeful circulatory occlusion may enhance exercise performance. The value of IPC for improving performance is controversial owing to challenges with employing effective placebo controls. This study examines the efficacy of IPC versus a deceptive sham protocol for improving performance to determine whether benefits of IPC are attributable to true physiological effects. It was hypothesized that IPC would favorably alter performance more than a sham treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…One limitation of this study was that participants were not completely blinded during the study. The presence of the placebo effect in IPC experiments remains controversial, with some studies finding [34,35] and others not findings evidence for this [7,36]. The use of placebo is a standard control component of most clinical trials, and it attempts to clarify the potential effect of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One limitation of this study was that participants were not completely blinded during the study. The presence of the placebo effect in IPC experiments remains controversial, with some studies finding [34,35] and others not findings evidence for this [7,36]. The use of placebo is a standard control component of most clinical trials, and it attempts to clarify the potential effect of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that SHAM induced similar levels of discomfort to IPC but comparable exercise performance outcomes to the CON [7]. In the study of Cheung et al [36], they informed participants that the effects of IPC and SHAM on exercise performance were unclear before starting the study, and used the therapeutic ultrasound procedure as SHAM condition. They reported that 69% of participants believed that IPC would hinder exercise performance, whereas SHAM ultrasound could improve performance [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite 73% of participants expecting their performance to improve following the sham condition, only IPC improved swimming performance relative to the control. Similarly, Cheung et al (2020) reported improved cycling time-to-exhaustion following IPC despite participants reporting negative performance expectations after IPC and positive performance expectations after their sham.…”
Section: Is Ipc a Placebo Effect?mentioning
confidence: 90%
“…It is not recommended that BFR be used prior to explosive activities due to BFR exercises being performed at or near volitional fatigue. While it is early to make any definitive conclusions, there is some early evidence that ischemic preconditioning may enhance recovery after athletic performance, [45][46][47][48][49] but evidence to the contrary exists as well. 50,51 While BFR appears to be a very promising and exciting innovation in our field, it is important to keep in mind that accepted, proven training practices and principles are not abandoned.…”
mentioning
confidence: 99%